Late Miscarriage and HHV-6 Meningoencephalitis: A Case Report - Bonassisa, Silvia; Aquino, Carmen Imma; Libretti, Alessandro; Amadori, Roberta; Remorgida, Valentino; Surico, Daniela (International Journal of Innovative Research in Medical Science, 2023)
Human Herpesvirus 6 (HHV-6) is often associated with asymptomatic infections, but in immunocompetent adults is relatively rare. A 24-years old pregnant woman at 16 weeks of gestation presented a meningoencephalitis caused by HHV-6, confirmed by MRI (Magnetic Resonance Imaging) and cerebrospinal fluid (CSF) sample. Acyclovir treatment (750 mg IV for 3 times/die) was started but after hours the patient started a spontaneous labor arose which determined a late miscarriage at 16+5 weeks of gestation without evidence of intra-amniotic infection or chorioamnionitis. The patient was discharged after 3 weeks in good health and without neurological sequalae. The exact role of HHV-6 in the development of late miscarriage and its incidence in late abortions is currently unknown.